PENGARUH DESAIN PRODUK, PERAN INFLUENCER, PERCEIVED VALUE, DAN BRAND AWARENESS TERHADAP PEMBELIAN SEPATU ADIDAS - Kusumawati, Heni; Hasan, Wildan (Jurnal Akuntansi Dan Manajemen, 2025)
This study investigates the impact of product design, influencer role, perceived value, and brand awareness on the purchase decisions of casual Adidas shoes by Generation Z (aged 12-27) in Yogyakarta. Data were gathered via a questionnaire from 108 owners of original casual Adidas shoes. Multiple linear regression analysis was conducted using SPSS version 26, incorporating validity, reliability, classical assumption, and regression tests to assess the hypotheses. Findings reveal that product design (p<0.05), influencer role (p<0.05), perceived value (p<0.05), and brand awareness (p<0.05) each positively influence purchase decisions. The coefficient of determination (R²) of 64.2% indicates that these four variables account for the variation in purchase decisions among this demographic, with 35.8% attributed to external factors not covered in this research. The results underscore the significance of marketing strategies emphasizing appealing product design, influencer partnerships, enhanced perceived value, and strong brand awareness to boost purchase decisions.